2011
DOI: 10.1177/1099800411423807
|View full text |Cite
|
Sign up to set email alerts
|

Bone Status in Activity-Restricted Pregnant Women Assessed Using Calcaneal Quantitative Ultrasound

Abstract: Increased fracture risk appears to be a negative side effect incurred through an average of 16 days of hospitalized AR in late pregnancy. Further investigations using a larger sample size are necessary to evaluate the effect of antepartum AR on bone status in the postpartum period to determine if bone status is further attenuated by breastfeeding or if recovery occurs with resumption of ambulation and return of menses and to assess future risk in these women as they age. Prenatal care providers should be made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Data available suggest that hospitalized pregnant individuals self-impose bed rest even in the absence of a medical recommendation [20]. Studies on ambulatory third trimester pregnant individuals show a step count of 6495, hospitalized with partial or no bed rest prescribed, show that these individuals perform about 1300-1500 steps and indeed, the level of step counts in those with strict bed rest drops dramatically to 378 steps [21][22][23][24]. Since the activity levels of hospital-admitted pregnant individuals are drastically reduced, many show similar physiological side-effects to non-pregnant bed-rested individuals.…”
Section: Effects Of Hospitalization and Bed Rest In Pregnancymentioning
confidence: 99%
“…Data available suggest that hospitalized pregnant individuals self-impose bed rest even in the absence of a medical recommendation [20]. Studies on ambulatory third trimester pregnant individuals show a step count of 6495, hospitalized with partial or no bed rest prescribed, show that these individuals perform about 1300-1500 steps and indeed, the level of step counts in those with strict bed rest drops dramatically to 378 steps [21][22][23][24]. Since the activity levels of hospital-admitted pregnant individuals are drastically reduced, many show similar physiological side-effects to non-pregnant bed-rested individuals.…”
Section: Effects Of Hospitalization and Bed Rest In Pregnancymentioning
confidence: 99%
“…Postpartum bone density has been shown to be associated with activity restrictions due to high-risk obstetric conditions, body mass index (BMI), previous lactation periods, exercise, and other such factors. [4][5][6] However, the factors that can be intervened upon are still limited. It has been reported that an exercise program focusing on resistance exercise may be effective for preventing a decrease in bone density during the lactation period among women.…”
Section: Daily Physical Activity Is Associated With Increased Sonogramentioning
confidence: 99%
“…Bone resorption rapidly increased as bed rest was initiated. Last, in a recent pilot study of bone loss in the calcaneus assessed by quantitative ultrasound, the speed of sound and broadband attenuation scores were not significantly different after 7 days of bed rest between an ambulatory and bed-rest group [33]. However, bone stiffness index scores, were significantly different between the groups, suggesting a greater relative risk for fracture in the women treated with activity restriction.…”
Section: Physiological Side Effects Of Antepartum Bed-rest Treatmentmentioning
confidence: 99%